Quality and Efficacy of the Indigenous Tutorial Assistance Scheme (ITAS) for University Students - Whatman, Sue; McLaughlin, Juliana; Willsteed, Susan; Tyhuis, Annie; Beetson, Susan (The Australian Journal of Indigenous Education, 2008)
Abstract Designed as a “supplementary” tuition scheme, the Indigenous Tutorial Assistance Scheme (hereafter referred to as ITAS) is a strategic initiative of the National Indigenous Education Policy (DEET, 1989). This paper seeks to contribute to the literature of the analysis of the quality and efficacy of ITAS. Currently, the delivery of ITAS to Indigenous students requires enormous administration and commitment by the staff of Indigenous education support centres. In exploring the essential but problematic provision of ITAS to Indigenous university students, this paper provides insights into significant aspects of our program that move beyond assumptions of student deficit, by researching the quality of teaching and learning through ITAS, analysing administrative workload, and sharing innovations to our program as a result of participatory research with important ITAS stakeholders.